State and social power in post-communist countries: 1996–2022 - Monika Çule; Murray E. Fulton (Humanities & Social Sciences Communications)
Abstract The purpose of this paper is to provide a procedure for examining the extent to which the changes observed among post-communist countries are consistent with a dynamic determined by the relative power of the state versus the relative power of society as captured in Acemoglu and Robinson’s “narrow corridor” framework. A direct test of Acemoglu and Robinson’s theory is not possible because the available data measures the quality of government and not the underlying state and society power. However, estimates of these latent variables can be obtained with factor analysis and the calculation of factor scores, which are then used in a cluster analysis to group countries according to their estimated state and society power. The results of the cluster analysis show three distinct groups of post-communist countries; these groups are argued to have the characteristics of the Despotic Leviathan, the Paper Leviathan and the Shackled Leviathan. While we find support for Acemoglu and Robinson’s prediction that the Despotic Leviathan acts as an attractor, the other predicted attractor – the Absent Leviathan – is not found in the data. Instead, countries with low state and society power appear to be trapped in the Paper Leviathan group, thus suggesting that it may also be an attractor. As predicted, membership in the Shackled Leviathan is stable only if state and society power are both large and relatively balanced. A closer analysis of three countries – Russia (Despotic Leviathan), Albania (Paper Leviathan), and Hungary (unable to secure a place in the “narrow corridor”) – provides additional evidence that largely supports the use of factor and cluster analysis to categorize countries.